TPACK-universal design for learning for Malaysian intellectual disability education : low-high tech integration - Rosnani, Saini; Zaimuariffudin Shukri, Nordin; Mohd Hafizan, Hashim; Mohamad Taha, Abol (Institute of Advanced Engineering and Science (IAES), 2025)
The integration of technological pedagogical content knowledge (TPACK) and universal design for learning (UDL) in special education remains challenging, particularly for intellectual disabilities (ID) learners in East Malaysia. This study investigated how special education teachers utilize technology tools and integrate UDL principles with TPACK frameworks to support ID learners, addressing the need for inclusive education aligned with sustainable development goal 4 (SDG 4). Using a qualitative approach, data were collected through semi-structured interviews, classroom observations, and document analysis from four purposively selected special education teachers in two East Malaysian secondary schools offering special education integration programs (SEIP). Thematic analysis revealed three key findings: i) low technology supports for accessibility and engagement; ii) high technology integration for personalization and empowerment; and iii) integrating of TPACK and UDL principles challenges due to limited understanding and resource constraints. The study concluded that while teachers show commitment to technology use, there is a pressing need for targeted professional development to enhance TPACK and UDL competencies. These findings align with SDG 4’s focus on quality education for all, emphasizing how enhanced teacher training and effective technology integration can significantly improve the quality and inclusivity of education for ID learners.